Osteoblastoma of the frontal bone invading the orbital roof: A case report - Wang, Kun (Medicine (Baltimore), 2018)
RATIONALE: Osteoblastoma is an uncommon primary bone tumor that involves any part of the skeleton. But its occurrence in the skull is extremely rare. PATIENTS CONCERNS: A 30-year-old female was admitted to our hospital, because of the mass in the right frontal region with the history of headache for 3 years without nausea or vomiting. DIAGNOSIS: Initial differential diagnoses included hemangiopericytoma, atypical intraosseous meningioma, calvarial osteosarcoma, fibrous dysplasia, and histiocytosis, based on the results of enhanced CT and MRI. INTERVENTIONS: A total surgical resection of the mass was performed. OUTCOMES: Postoperative histopathologic analysis demonstrated the typical features of osteoblastoma, the benign bone neoplasm. Serial radiologic examination did not show recurrence in the 6 months follow-up. LESSONS: The radiologic appearance of the osteoblastoma is always confusing and makes the diagnosis difficult. We hope our case can give some clinical clues for the diagnosis and management of the disease.